DENOTATION, CONNOTATION AND MYTHICAL MEANING OF THE CIO TAO RITUAL’S WEDDING CEREMONY OF THE CHINESE-BENTENG COMMUNITY THROUGH THE SEMIO-PRAGMATICS APPROACH - Suratminto, Lilie (International Review of Humanities Studies, 2019)
Gobard (1976) divides language into four functions namely: vernacular function, vehicular function, cultural reference function and mythic religion function. An extinct language is not totally extinct but there is a shifting of function. Even though the language that become extinct, is not used anymore in communication function, it is still used to show cultural identity. Culture is one thing that characterize a group of population. According to Kroeber & Kluckohn in Suratminto et al (2017:25) culture is a pattern that implicitly and explicitly formed and at the same time also determines a collective symbol of customs that has different targets in every population group and is displayed in artefact form. The Chinese language of the Chinese-Benteng in Tangerang is also in danger of disappearing. They do not communicate with each other in the Chinese language. Most people do not speak nor write in Chinese characters, but they still maintain their culture in their everyday life. This research is focused on one of their preserved cultures of their ancestors called cio tao, in Tangerang. Cio tao is one of the wedding rituals. A few days before the wedding ceremony there is a sang jit ceremony. In this ceremony the candidate of the bridegroom comes to the parents of the bride‟s parents to hand over the dowry. The research was held in Kampung Naga on April 21th 2019 with qualitative methodology by visual recording and interviewing the respondent. Kampung Naga is one of the kampungs of the Chinese-Benteng in Tangerang district. There are many kampungs inhabited by the Chinese-Benteng e.g. Kampung Melayu, Tanjung Burung, Kampung Sangiang, Sewan, Karawaci, etc. Through the dimensional approach of the semio-pragmatic theory of Danesi & Perron (1998), the step by step process of the cio tao ritual will be analysed to know the goals of each sign determining whether it has a denotative, connotative or mythical meaning.